Efficiency of the pedagogical model of teaching the basic competitive swimming strokes to children with cerebral palsy. - Цибанюк, Олександра Олександрівна; Tsybanyuk, Oleksandra (My University, 2021)
According to many scholars, sport is essential for social adaptation and integration of people with disabilities. Therefore, it is important to research innovative technologies for teaching competitive swimming technique to 8-10-year- old children with cerebral palsy. The aim of this study is to develop the technology of teaching competitive swimming techniques to children with cerebral palsy and to evaluate its effectiveness for mastering the front crawl swimming technique. Materials and methods: analysis of scientific literature, questionnaires (e-correspondence), pedagogical experiment, expert survey, determination of the coefficient of technique efficiency, statistical methods. A total of 15 qualified swimming coaches participated in this study. The experiment involved 29 children who were diagnosed with cerebral palsy. Results: the main means of technology implementation is the web-based information system SwimCP (Swimming with Cerebral Palsy), which promotes effective swimming teaching for children with cerebral palsy at the initial stage of sports training by selecting and recommending an approximate complex of exercises that take into account the peculiarities of motor disturbance in accordance with the specific form of cerebral palsy and the stage of motor activity training. Conclusion: using expert assessment and the coefficient of swimming technique efficiency determination, it is confirmed that the proposed technology of teaching basic competitive swimming techniques to children with cerebral palsy is effective. Citas
Keywords: Cerebral palsy, Pedagogical model, Swimming stroke, Front and Back crawl stroke